Strategies of Islamic Religious Education Teachers in Curriculum Development in Indonesian Junior High Schools - Rahmi, Husnatur; Ilham, Seprian; Safarudin, Rizal (Ahlussunnah: Journal of Islamic Education, 2026)
Although studies on Islamic Religious Education curriculum development have been widely conducted, research specifically examining teachers’ strategies within school-level practices remains limited. This study investigates teachers’ strategies in developing the Islamic Religious Education curriculum at the junior high school level. This study employs a qualitative approach with a case study design, with data collected through interviews, observations, and document analysis. The findings reveal that teachers’ curriculum development strategies encompass four main stages; in-depth understanding of the curriculum, systematic instructional planning, contextualized teaching implementation, and continuous evaluation. In addition, this study identifies supporting factors, including teachers’ professional competence, institutional support, and the availability of facilities and infrastructure, as well as constraining factors such as limited instructional time and diverse student abilities. These findings highlight the strategic role of teachers in ensuring the effectiveness and relevance of the curriculum to students’ needs. This study contributes to the development of Islamic education curriculum discourse by emphasizing the importance of teacher-centered strategies in dynamic educational contexts.